Analisis Pengelolaan Keuangan Remaja (Usia 18-22) terhadap Risiko Terjadinya Malnutrisi - Abdi, Aurell Vinaya; Ali, Muhamad; Meyzawinata, Nabil Abdillah; Safitri, Risa Nur; Meydiawanti, Salsabilla; Amanda, Shafira Putri; Rozak, Rama Wijaya Abdul (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Finances are the most crucial thing in human life, therefore good financial management is very necessary for a better life. Moreover, in this case it concerns the risk of malnutrition in today's teenagers if they cannot manage their finances well. The aim of this research is to determine teenagers' financial management strategies regarding the risk of malnutrition and also the perceived impacts. Then, the research method used is a descriptive qualitative research method and analysis techniques used through the process of data reduction, data presentation, and drawing conclusions. The results of this research show that regarding teenagers' financial management strategies, several things can be done, namely making a list or list of needs, limiting expenses, and consuming home- cooked or homemade food. Then the impacts felt include teenagers becoming more frugal, choosing basic necessities, especially food, becoming more regular, and finances not being overdrawn and being able to be saved. Keywords: Finance, Malnutrition, Management, Teenagers,